MATURITY RELATED VARIATION IN ANAEROBIC PERFORMANCE AMONG YOUNG MALE ATHLETES AND NONATHLETES - ALPAY GÜVENÇ; ALPER ASLAN; CANER AÇIKADA (ümit doğan üstün, 2018)
The aim of the present study was to assess the influence of maturation and regular sport participation on anaerobic performance variables of 11-to 15-year-old young male athletes and non-athletes. One hundred fifty young male subjects were voluntarily participated in this study. Trained boys (n=75), comprised of 27 Handball, 26 Soccer and 22 Volleyball players, had been training regularly for at least one year. However, untrained boys (n=75) were not involved in any systematic training program. Participants were also divided into five maturity groups according to Tanner's stages. Body mass and stature were determined. Percentage of body fat and fat free mass were also calculated from the appropriate equations. Anaerobic performance was evaluated with the Wingate Anaerobic Test. Two-way Analysis of Variance (2×5) with Tukey's-HSD was used for statistical analysis. Pearson's correlation coefficients were also computed. The results revealed that absolute anaerobic performance variables were highly positively correlated with body mass and fat free mass, significantly increase with maturation (p<0.01). Maturation effect on anaerobic performance variables remained even when body mass and fat free mass were factored out (p<0.01). The trained boys have higher anaerobic performance values and relatively steeper increase with maturation compared to untrained group. Finally, there were no interaction effects between maturation and training groups on any of the variables. In conclusion, variations in anaerobic performance levels are partly determined by factors other than body mass or fat free mass. This finding may be due, in part, to the maturation-related functional and metabolic changes in skeletal muscle.